A study on reducing digital piracy: an analytical network process approach with benefits, opportunities, costs and risks analysis - Nunes, Tiago Gil Fachada (2013)
Dissertação para obtenção do Grau de Mestre em Engenharia e Gestão IndustrialThe world and the information technology in general has in recent years undergone a major transformation due to rapid technological innovations that became universally available to all. These innovations that are constantly being introduced bring an increasing ease of access, use, mobility and other gains which in turn are also facilitators to illegal activities, allowing for the acquisition of products that are identical to the original without there being any loss of quality in the copy process. This led to technologies that were created in order to prevent such practices of digital piracy and give more control to those who own the intellectual property rights, known as Digital Rights Management (DRM) technologies. The application of these technologies has brought new problems, such as excessive restrictions that do not satisfy consumers and may harm society in general by restricting the freedom of use and exchange of ideas. Although there is scientific work on this issue, there has never been applied a multi-criteria analysis to assist in the decision making of what could be the best solution to reduce digital piracy. By developing an analytical network process (ANP) model with analysis of benefits, opportunities, costs and risks (BOCR), this dissertation seeks to fill the gap in the scientific community with the implementation of a multi-criteria decision making process to determine the best alternative for this problem. Finally, in this dissertation there is also a practical application of the developed model in the national digital books area